A Study on Marital Satisfaction of Women Working in Southern Railways Tiruchirappalli - Velmurugan, K.S.; Maheswari, Dr.K. (International Journal of Scientific Research and Management (IJSRM), 2017)
Marital satisfaction is an essential element for successful family life and personal growth. The fulfillmentand positive development will be possible only when the relationship between couples is coherent andsatisfactory (Azeez, 2013). Different factors have significant influence on the marital satisfaction, likepersonality of the partner, nature of job, child rearing responsibility, sexual satisfaction and communicationpatterns are some of the examples. The active engagement of women’s in the employment sector and theirdual role has significant correlation with the marital satisfaction, especially in a society like India. Thisstudy is aimed to assess marital satisfaction of women working in southern railways, Tiruchirappalli.Objective of the study includes socio demographic of the respondents and assessment of marital satisfactionof women working in southern railways, Tiruchirappalli. The researcher has used descriptive researchdesign and simple convenient sampling method was adopted to enquire 56 respondents for the study. Theresearcher used self prepared interview schedule pertaining to socio-demographic characteristics and astandardized tool on the marital satisfaction developed by Brunda Amirthraj and Indira Jai Prakash (1985).Majority of the respondents (78.6%) educational qualification had professional course, nearly half of therespondents (48.2%) had family members five to seven members. More than half of the respondents havemoderate level of marital satisfaction